Investigation of tensile strength and dimensional variation of T700 carbon fibres using an improved experimental setup. (February 2020) - Islam, Faisal; Joannès, Sébastien; Bucknell, Steve; Leray, Yann; Bunsell, Anthony; Laiarinandrasana, Lucien
Knowledge of fibre strength is crucial for understanding the failure behaviour of fibre-reinforced composite materials and structures. Measuring the properties of technical fibres has been known to be very challenging, and the different challenges associated with single fibre characterisation are illustrated in this article. An improved and automated experimental methodology for tensile testing of single fibres is described. This process has been used to generate fibre strength data for T700 carbon fibres at three different gauge lengths of 4, 20 and 30 mm. The variability in strength and modulus of short fibres was found to be much larger than that of longer fibres. Statistical analysis of this large data set has also highlighted the limitations of the standard Weibull distribution for representing fibre strength behaviour. The need for a better statistical representation of the fibre strength data in order to provide a more accurate description of the fibre strength behaviour has been emphasized.